Does the Tough Stuff Make Us Stronger? Spiritual Coping in Family Caregivers of Persons with Early-Stage Dementia - Jocelyn Shealy McGee; Morgan Davie; Rebecca Meraz; Dennis Myers; Stephanie Clintonia Boddie (Religions, 2022)
Spiritual coping may be conceptualized as relying upon spiritual beliefs, practices and/or relationships as an aspect of navigating stressful or traumatic experiences. There is evidence that spirituality may be used as a resource and may cultivate growth for some in the midst of difficult life circumstances. There is limited research, however, on this phenomenon among family caregivers of persons living with a dementia, particularly those in the early stages. The purpose of the current study, therefore, was to gain insight into the nature of spiritual coping among caregivers of persons living with a dementia in the early part of their caregiving journey. Using interpretative phenomenological analysis, interviews with 28 caregivers were analyzed. Five spiritual coping themes and corresponding subthemes emerged from their narratives: (1) spiritual relational coping; (2) spiritual behavioral coping; (3) spiritual belief coping; (4) spiritual coping to gain a sense of control; and (5) spiritual coping for constancy or life transformation. Three-fourths of the sampled caregivers reported growth in their spiritual lives during the early part of their caregiving journey. A sense of being “spiritually grounded” in the Divine (e.g., God, a higher power, a life philosophy) and oneself (as a spiritual being) was an important aspect of spiritual coping in this sample. Additionally, caregivers tended to use multiple forms of spiritual coping simultaneously while also navigating spiritual struggles. Finally, some caregivers viewed caregiving as a spiritual path that they were actively following rather than a passive spiritual experience. These findings speak to the importance of identifying and encouraging spiritual coping among caregivers as well as identifying spiritual struggles.